2014
DOI: 10.1039/c4ob01142b
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of fluoxetine and duloxetine through an in situ imine formation/borylation/transimination and reduction approach

Abstract: We report efficient, catalytic, asymmetric total syntheses of both (R)-fluoxetine and (S)-duloxetine from α,β-unsaturated aldehydes conducting five sequential one-pot steps (imine formation/copper mediated β-borylation/transimination/reduction/oxidation) followed by the specific ether group formation which deliver the desired products (R)-fluoxetine in 45% yield (96% ee) and (S)-duloxetine in 47% yield (94% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…Similar reactions were also conducted in an attempt to make the β-boryl aldehyde by initially converting the α,β-unsaturated aldehyde in situ into the respective imine, followed by catalytic borylation and then workup; however, the product was extremely unstable, and therefore, subsequent Wittig olefination was used to facilitate the generation of a stable and versatile homoallylic boronate ester . Furthermore, starting from the α,β-unsaturated aldehyde, such a process has been utilized in the total syntheses of ( R )-fluoxetine and ( S )-duloxetine …”
Section: Boryl Addition (Hydroboration) Reactionssupporting
confidence: 62%
See 1 more Smart Citation
“…Similar reactions were also conducted in an attempt to make the β-boryl aldehyde by initially converting the α,β-unsaturated aldehyde in situ into the respective imine, followed by catalytic borylation and then workup; however, the product was extremely unstable, and therefore, subsequent Wittig olefination was used to facilitate the generation of a stable and versatile homoallylic boronate ester . Furthermore, starting from the α,β-unsaturated aldehyde, such a process has been utilized in the total syntheses of ( R )-fluoxetine and ( S )-duloxetine …”
Section: Boryl Addition (Hydroboration) Reactionssupporting
confidence: 62%
“…533 Furthermore, starting from the α,β-unsaturated aldehyde, such a process has been utilized in the total syntheses of (R)-fluoxetine and (S)-duloxetine. 534 A novel copper(I) bifluoride NHC complex showed relatively high activity for the β-borylation of an α,βunsaturated ester (Scheme 65); however, a copper complex with a chiral NHC ligand used in the study showed poor yield and enantioselectivity. 535 Borylations of α,β-unsaturated carbonyls using bulky copper(I) phosphine catalysts and B 2 (OH) 4 have also been reported.…”
Section: Unsaturated Carbonylsmentioning
confidence: 99%
“…Data in agreement with the literature. (Calow et al 2014). Aminoketone hydrochloride 3b (105 mg, 0.5 mmol) and NaBH4 (39 mg, 1.0 mmol) were added into a 25 mL stainless steel grinding jar with a 25 mm Ø stainless steel ball.…”
Section: General Methods and Considerationsmentioning
confidence: 99%
“…133 Several chemical methods, in addition to enzymatic methods utilizing lipases or lyases (section 2.1.4 and 2.1.5), were developed for the synthesis of (S)-duloxetine. 130 However, chemical methods, ranging from Noyori-based asymmetric hydrogenations, 134 enantioselective allylation, 135 boronane-based asymmetric reductions, 136 to asymmetric aldol condensations, 137 mostly give reduced yields and lower e.e. 's compared to the presented biocatalytic reduction.…”
Section: Alcoholsmentioning
confidence: 99%